Terpaan Pemberitaan Layanan Pemadam Kebakaran di Media Online: Pengaruh terhadap Reputasi Pemerintah Kota Jakarta Selatan - Fina abiyya Agustin Mubarokah; Tria Patrianti (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the effect of media coverage of the Fire and Rescue Department’s services in online media on the reputation of the South Jakarta City Government among residents of RT 12, RW 05, Pondok Pinang Village. The approach used was an explanatory quantitative study employing a survey method involving 97 respondents selected through purposive sampling. Data were collected using a structured questionnaire based on a Likert scale and analyzed using descriptive and inferential statistics via SPSS software. The results indicate that the level of media coverage falls into the high category with an average score of 3.32, while the government’s reputation is in the high category with an average score of 3.27. The correlation test yielded a value of 0.940, indicating a very strong relationship, and a coefficient of determination of 0.884, indicating a significant contribution of news exposure to government reputation. Hypothesis testing also revealed a statistically significant effect. These findings confirm that online media plays a crucial role in shaping public perception and strengthening government reputation through the effective dissemination of public service information.